Effect of Bi-substitution into the A-site of multiferroic La0.8Ca0.2FeO3 on structural, electrical and dielectric properties. Issue 27 (23rd April 2020) - Issaoui, H.; Benali, A.; Bejar, M.; Dhahri, E.; Costa, B. F. O.; Graca, M. P. F.; Valente, M. A.
Abstract : (La0.8 Ca0.2 )1− x Bi x FeO3 ( x = 0.00, 0.05, 0.10, 0.15 and 0.20) (LCBFO) multiferroic compounds have been prepared by the sol–gel method and calcined at 800 °C. Abstract : (La0.8 Ca0.2 )1− x Bi x FeO3 ( x = 0.00, 0.05, 0.10, 0.15 and 0.20) (LCBFO) multiferroic compounds have been prepared by the sol–gel method and calcined at 800 °C. X-ray diffraction results have shown that all samples crystallise in the orthorhombic structure with the Pnma space group. Electrical and dielectric characterizations of the synthesized materials have been performed using complex impedance spectroscopy techniques in the frequency range from 100 Hz to 1 MHz and in a temperature range from 170 to 300 K. The ac-conductivity spectra have been analysed using Jonscher's power law σ ( ω ) = σ dc + Aω s, where the power law exponent ( s ) increases with the temperature. The imaginary part of the complex impedance ( Z ′′) was found to be frequency dependent and shows relaxation peaks that move towards higher frequencies with the increase of the temperature. The relaxation activation energy deduced from the Z ′′ vs. frequency plots was similar to the conduction activation energy obtained from the conductivity. Hence, the relaxation process and the conduction mechanism may be attributed to the same type of charge carriers. The Nyquist plots ( Z ′′ vs. Z ′) at different temperatures revealed the appearance of two semi-circular arcs corresponding to grain and grain boundary contributions.